Synthesis and characterization of natural extracted precursor Date Palm Fibre-based activated carbon for Aluminum removal by RSM optimization - Basheer A.O.; Hanafiah M.M.; Alsaadi M.A.; Al-Douri Y.; Malek M.A.; Aljumaily M.M.; Fiyadh S.S. (MDPI AG, 2023)
The Powder-Activated Carbon (PAC) under optimum conditions from a new low-cost precursor Date Palm Fibre (DPF) biomass through a carbonization followed by KOH activation has been synthesized by response surface methodology (RSM) combined with central composite design (CCD). The special effects of activation temperature, time, and impregnation ratio on bio-PAC Aluminum (Al3+) removal and uptake capacity were examined. The optimum conditions for synthesized bio-PAC were found to be 99.4% and 9.94 mg g-1 for Al3+ removal and uptake capacity, respectively at activation temperature 650 C, activation time 1h and impregnation ratio 1. The optimum bio-PAC was characterized and analyzed using FESEM, FTIR, XRD, TGA, BET, and Zeta potential. RSM-CCD experimental design was used to optimize removal and uptake capacity of Al3+ on bio-PAC. Optimum conditions were found to be at bio-PAC dose of 5 mg with pH 9.48 and contact time of 117 min. Furthermore, at optimized conditions of Al3+ removal, kinetic, and isotherm models were investigated. The results reveal the feasibility of DPF biomass to be used as a potential and cost-effective precursor for synthesized bio-PAC for Al3+ removal. 2019 by the authors.